2019
DOI: 10.1111/cob.12298
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among bariatric surgery candidates: The roles of body image and emotional eating

Abstract: The increased risk of psychological distress among bariatric surgery candidates may be attributed, at least in part, to body image dissatisfaction (BID). The aim of the present study was to test the hypotheses that body image could be correlated with the psychological distress variables, and that emotional eating behaviours could mediate the relationship between body image and psychological distress. A sample of consecutive participants seeking bariatric surgery (N = 169, 67% females, mean age, 41.8 years [SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
2
18
0
2
Order By: Relevance
“…The original English version of these three questionnaires were translated to Hebrew in previous studies (for details see [15]).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The original English version of these three questionnaires were translated to Hebrew in previous studies (for details see [15]).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence has shown that extremely obese individuals, especially females, are generally less satisfied with their bodies than the normal-weight population [3]. Furthermore, BID was found related to weight-related stigma, lower self-esteem, overt discrimination, increased symptoms of depression [9,10], anxiety [11,12], psychiatric problems, [13,14], and suicidality [15] among bariatric surgery patients. Monitoring and identifying the underlying mechanisms involved in the psychological well-being of bariatric surgery candidates is, therefore, vital, as it may improve surgery preparation and thereby promote greater satisfaction with the process.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations